Formação de professores para a Era da Conexão Móvel: um estudo reflexivo sobre as práticas da cultura móvel e ubíqua - Cônsolo, Angeles Treitero García (2014)
This research contains a study on mobile devices, more precisely mobile telephony applied to educational purposes. The general aim here is to investigate the absence of methodologies in degree courses, related to the use of Information Technology and Communication (ICTs), in order to incorporate the use of mobile telephony. The target is to identify relevant procedures a professor should incorporate in his/her pedagogical practices in order to face the challenges mobile technology poses for the teaching-learning process in the beginning of the 21st century. More specific objectives of this paper are the verification of the political and instructional use of the ICTs in Brazilian Education; an analysis of the pedagogical potentialities and the reflexes mobile phones currently cause in Brazilian Education; and a thorough examination of the concept of mobility, when considering the use of such technology. Whereas this paper involves several areas of knowledge, the theoretical approach has a multi-disciplinary character, since the early stages of written communication in societies and along its development. This work includes a discussion on the possibilities mobile technology provides regarding the access to information and to communication, and the challenge future professors should have concerning education. After a field research, an analysis of the uses of mobile phones and their applicability, as well as an analysis of what professors and degree students think of the use of such technology in Education were developed, allowing the discussion of the current need of new pedagogical practices when performing the teaching profession. Such field research was carried in three universities of the private sector, with the participation of professors and students of degree courses. All of them answered a questionnaire with open and closed questions, with the collection of quantitative and qualitative data. This paper includes five chapters: in the first chapter I present the research project; in the second, I discuss the influence of ICTs in Brazilian Education; in the third one I present some reflections on the question and statistical data regarding the potentialities mobile technology provides; in the fourth chapter, I discuss the concept of mobility and suggest some of the questions posed to degree professor when dealing with projects including such technology; in the last one, I present an analysis of the field research results. As a result of this work, one concludes that professors are not yet considering the possibility of using that kind of technology to support education. Such use is viable, as long as it becomes part of pedagogical projects in schools and of the curriculum. The involvement of all school community is also necessary. Additionally, educational institutions must offer conditions for professors to keep themselves updated and get ready to engage in new activities with students. This paper shows that mobile devices, like any other kind of technology, are one more possible tool to be used on a daily basis by educators. Like many other procedures and resources, the use of Information Technology and Communication will not solve, by itself, the educational problems in Brazil